PENGARUH EKSTRAK ETANOL SIMPLISIA PEGAGAN (Centella asiatica (L.) Urban) TERHADAP PERTUMBUHAN Candida albicans - Nourma Priska Dianggi Tamba (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Background: Candidiasis is a common fungal infection in Indonesia. Some examples of chemical antifungal drugs include those from the azole group such as ketoconazole, but these antifungal drugs have weaknesses. Therefore, several previous researchers have found another alternative that has the potential to be a natural antifungal, namely (Centella asiatica (L.) Urban).Purpose: The purpose of this study was to prove the antifungal activity of the ethanol extract of pegagan simplicia on the growth of Candida albicans.Methode: The study was using an experimental method with concentration variations of 5%, 10%, 15%, 20% and 25% on each ethanol extract of pegagan simplicia. In this study, diffusion disk Kirby-Bauer was use and Ketoconazole 2% antifungal was use as a positive control and 10% DMSO as a negative control. Data analysis in this study was analyze qualitatively, by processing data and analyzing factors related to research by presenting data in the form of words, sentences, and pictures.Result: The results of phytochemical tests showed that ethanol extract of pegagan simplicia containing saponins and tannins. Ethanol extract of pegagan simplicia are not able to inhibit the growth of Candida albicans by disc diffusion method.Conclusion: In this study, it was found that the ethanol extract of pegagan simplicia did not form an inhibition zone for the growth of Candida albicans Keywords: candidiasis, simplisia pegagan, antifungal